Implementasi Pendekatan Filosofis dalam Studi Islam - Wahyuni, Sri; Kholid, Kholid (TSAQOFAH, 2025)
Mindset affects the pattern of human life. Where the mastery of knowledge owned by humans also affects the mindset and pattern of human life. In life, to do something must be balanced with knowledge, especially when the context is a religious issue. In addition, existing thoughts are developed into critical thinking. Therefore, it is important that everyone understands to the extent that they can implement a philosophical approach. So that it can be one of the efforts to help in solving the problems faced. The method in this research is to use a descriptive method that provides a descriptive explanation of the results of data collection through literature studies. Which provides results regarding an overview of how the implementation of the philosophical approach in Islamic studies.